Sex Stereotypes: An Artifact in Leader Behavior and Subordinate Satisfaction Analysis? - Osborn, Richard N.; Vicars, William M. (Academy of Management Journal, 1976)
Data from two organizations revealed no consistent effect of leader sex on either leader behavior or subordinate satisfaction. The results fit a pattern of research evidence that shows sex stereotypes may be important in some laboratory settings but not in long-term situations. Thus some laboratory findings may be artifactual.